Solve the pair of simultaneous equation

Y=xsquared-x+3
Y=6-3x

5 answers

you probably want to wait for one of the admins to check it, but I think the answer may be 1. if x^2 + 2x=3, the only one that makes it true is 1.
y = x^2 - x + 3
3 x = 6-y or x = 2 - y/3
so
x^2 = 4 -4y/3 + y^2/9
then y = 4 - 4y/3 + y^2/9 -2 +y/3 + 3
y^2/9 - 2 y + 7 = 0
y^2 - 18 y + 63 = 0
(y-21)(y+3) = 0
I get 21 and -3
but matty is right, 1 works
y=x^2-x+3
y=6-3x
so, set them equal
x^2-x+3 = 6-3x
x^2+2x-3 = 0
(x+3)(x-1) = 0
x = 1 or -3
Thanks much couldn't have done it without ur help.. no fully understand but thanks..